The Role of Social Capital and ICT in Corporate Social Responsibility in a Developing Economy: An Empirical Study of the Finance Industry in Sri Lanka - Nawinna, D.; Venable, John (Association for Information Systems, 2016)
Social Capital (SC) has been recognised as an important factor in developing relationships of trust, providing the foundation for greater collaboration among individuals, groups, organisations, industries or countries, which is essential for enabling developing economies. Similarly, Corporate Social Responsibility (CSR) is touted as a key enabler of both organisational performance and of sustainable development, which are also essential for developing economies. Moreover, SC has significance as the basis for and the development of stakeholder relationships, which are essential to CSR. Information Systems (IS) researchers have become increasingly interested in exploring SC in relation to Information and Communications Technology (ICT). However, the combined effect of SC and ICT on the CSR in developing contexts remains unexplored. What role, if any, does ICT play in strengthening the relationship between SC and CSR? This study investigates the relationships between SC, ICT, and CSR in the developing economy context. Using a quantitative approach combining network science and structured equation modelling (SEM) to analyse both primary and secondary data, the study develops a model of the significant relationships theorised and confirmed in the analysis. The findings of this study provide new knowledge in both social capital theory and network theory, contributing to a more holistic perspective that incorporates social, technical and organisational aspects and provides insights useful for building effective strategies in similar developing contexts.